The Economics of Structural Change Volume I: Economic Structure and Change: Concepts and Theories - Hagemann, Harald; Landesmann, Michael; Scazzieri, Roberto (Cheltenham: Edward Elgar Publishing Limited, 2003)
These volumes constitute a remarkably comprehensive collection of seminal articles on structural change, including historical works such as Adam Smith on the division of labor and Karl Marx on reproduction schemes and modern pieces by Leontief, Sraffa, Pasinetti, Goodwin, Baumol, Arrow, Aghion and Howitt. Structural change analysis has been a distinctive feature of economics since its formative period. This authoritative three-volume collection presents a comprehensive selection of the key contributions to the topic. The Economics of Structural Change shows the central role that compositional dynamics plays in the analysis of fluctuations, development, employment and economy-environment interactions. Volume I covers concepts and theories in the economics of structural change; Volume II includes specific contributions to structural theories of growth, cycles and technological change; Volume III focuses on specific areas in the empirics of structural change analysis.
Includes bibliographical references and index.
rpm 09/09/13
Loans
Keywords: Economics; Economics- Mathemetical models; Industrial organization